2018
DOI: 10.1016/j.carbon.2018.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Comparative nanostructure analysis of gasoline turbocharged direct injection and diesel soot-in-oil with carbon black

Abstract: a b s t r a c tTwo gasoline turbocharged direct injection (GTDI) and two diesel soot-in-oil samples were compared with one flame-generated soot sample. High resolution transmission electron microscopy imaging was employed for the initial qualitative assessment of the soot morphology. Carbon black and diesel soot both exhibit core-shell structures, comprising an amorphous core surrounded by graphene layers; only diesel soot has particles with multiple cores. In addition to such particles, GTDI soot also exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 61 publications
(123 reference statements)
5
29
1
Order By: Relevance
“…Subsequently, the nanostructure determined by the image processing method is compared for the different soot and carbon black samples. Similar work has been performed by Pfau et al (2018) comparing the nanostructure af carbon black and soot-inoil from gasoline and diesel engines…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Subsequently, the nanostructure determined by the image processing method is compared for the different soot and carbon black samples. Similar work has been performed by Pfau et al (2018) comparing the nanostructure af carbon black and soot-inoil from gasoline and diesel engines…”
Section: Introductionmentioning
confidence: 67%
“…Huang and Vander Wal (2016) demonstrated the dependence of the nanostructure of soot particles upon partial premixing and the associated changes in the gas-phase chemistry of ethylene-air Bunsen flames. The collocation of layered graphene-like structures measured by their length, separation distance and curvature as well as defects within the crystallite structure (Bhardwaj et al 2014;Lapuerta et al 2012;Vander Wal and Tomasek 2003;Pfau et al 2018) altogether affect the reactivity of soot. Reactivity of soot, therefore, is a consequence of both agglomerate morphology and the nanostructure and chemical composition of primary particles (Pfau et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This particle formation process in the case of butanol is expected to promote primary particles growth. This is as a consequence of the combustion conditions, favour particle nucleation (high temperatures) and surface growth (isolate rich areas) [5], in which hydrocarbon in gas phase and hydrocarbon fragment are accreted to the nuclei, leading to a planar growth of PAH.…”
Section: Resultsmentioning
confidence: 99%
“…Under such conditions the fuel direct injection process is reported to lead to inhomogeneity of the air-fuel mixture and consequently incomplete fuel combustion, resulting in increased formation of soot [3]. Earlier studies have concluded that particulates in GDI engines are formed due to i) the locally fuel rich regions during the combustion process even in homogeneous mixtures at the macro scale [4], ii) piston wetting that leads to wall fuel-film formation as a consequence of the fuel injection process [5] and, iii) the carbonisation of non-combusted fuel droplets [6,7]. Factors affecting soot formation are highly related to the chemical structure and thermo-physical properties of the fuel used in combustion process, in addition to local equivalence ratio and in-cylinder temperature.…”
Section: Impact Of Bio-alcohol Fuels Combustion On Particulate Mattermentioning
confidence: 99%